Current Trends and Research Topics Regarding Intestinal Organoids: An Overview Based on Bibliometrics - Zhang, Meng-Meng; Yang, Ke-Lu; Cui, Yan-Cheng; Zhou, Yu-Shi; Zhang, Hao-Ran; Wang, Quan; Ye, Ying-Jiang; Wang, Shan; Jiang, Ke-Wei (Frontiers in Cell and Developmental Biology, 2021)
Currently, research on intestinal diseases is mainly based on animal models and cell lines in monolayers. However, these models have drawbacks that limit scientific advances in this field. Three-dimensional (3D) culture systems named organoids are emerging as a reliable research tool for recapitulating the human intestinal epithelium and represent a unique platform for patient-specific drug testing. Intestinal organoids (IOs) are crypt–villus structures that can be derived from adult intestinal stem cells (ISCs), embryonic stem cells (ESCs), or induced pluripotent stem cells (iPSCs) and have the potential to serve as a platform for individualized medicine and research. However, this emerging field has not been bibliometric summarized to date. Here, we performed a bibliometric analysis of the Web of Science Core Collection (WoSCC) database to evaluate 5379 publications concerning the use of organoids; the studies were divided into four clusters associated with the current situation and future directions for the application of IOs. Based on the results of our bibliometric analysis of IO applications, we systematically summarized the latest advances and analyzed the limitations and prospects.